PANEN RAYA KELAS SEJARAH: AN EXHIBITION-BASED DIFFERENTIATED HISTORY CLASSROOM TO ENHANCE 21ST CENTURY 4C SKILLS - Wilis, Roro; Kumalasari, Dyah (Universitas Labuhanbatu, 2025)
Purpose—This research aims to explore the implementation of the exhibition-based differentiated classroom